The Welfare Level Of Fisherman Household Of Napangga Lake At Tanjung Medan Village Tanjung Medan Subdistrict Rokan Hilir Regency Riau Province - Dedy Winta Nainggolan; Ramli '; Hamdi Hamid (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research was conducted at Napangga Lake Tanjung Medan Village Tanjung Medan Subdistrict Rokan Hilir Regency on march 2015. This research was aimed to analyse the welfare level of fisherman household of Napangga Lake Tanjung Medan Village. The method used is survey method. The respondents is determined by using simple random sampling. This research uses by indicator of BKKBN, BPS and UMR. Tanjung Medan district has 4278 inhabitants consists 2.219 males and 2.059 females. Their incomes are about Rp 800.000 to Rp 1.500.000 per month and the number of dependents are 5 to 6 people. From 33 families as respondents, BKKBN afford 20 families (62,5%) that included to disadvantages families, the BPS afford 2 families as poor families and the last indicator, UMR, shows that, the most of the households are poor, because their income underthan the regional minimum wage of Rokan Hilir Regency which is 1.520.000 per month.Keywords : Welfare, Fisherman household, Napangga Lake